Del texto dramático al hecho teatral: una adaptación de Hamlet en la Universidad Nacional de Río Cuarto - Engert, Valeria (Revista de Culturas y Literaturas Comparadas, 2021)
To read critically, as a socio-cultural practice, activates a complex web of relations which should involve the complexity of images, an integral part of our worldview. In our present context, images, be them static or in movement, exhibit a vital presence in meaning making processes, however, teaching-learning processes at university level continue to privilege the written word. In our research team on visual literacy (161/2016) we meant to explore the word image tension in a project that focused on the relation between literature and performance in an experience in which the Shakespearian text, translations and rewritings converge. The project Literature and performance: Approaching the Shakespearian text (carried out from May to November 2016, CD 138/2016) aimed at an interrogation and problematization of notions of representation beyond territorial, linguistic, disciplinary and cultural borders. Designed as a workshop, the project meant an out of the classroom experience that invited current students, former students, and teachers to work with bodies in action. The objective of this paper is to share the workshop experience that ended in a mise en scene proposal on December 13th, 2016, in the independent theatre El Mascaviento in Rio Cuarto, Córdoba.